2012
DOI: 10.7314/apjcp.2012.13.9.4683
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor Beta-1 C-509T Polymorphism and Cancer Risk: A Meta-analysis of 55 Case-control Studies

Abstract: Aim: To investigate the association of transforming growth factor-beta 1 (TGF-β1) C-509T polymorphism and susceptibility to cancer by means of meta-analysis. Methods: An extensive search was performed to identify eligible case-control studies investigating such a link. The strength of the association between TGF-β1 C-509T polymorphism and cancer risk was assessed by pooled odds ratios (ORs) and 95%confidence intervals (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
2
13
0
Order By: Relevance
“…Previous meta-analyses on this topic have yielded conflicting results [28][29][30][31][32]. The results of metaanalyses by Xiang et al [28], Liu et al [30], and Li et al [31] were similar to ours.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous meta-analyses on this topic have yielded conflicting results [28][29][30][31][32]. The results of metaanalyses by Xiang et al [28], Liu et al [30], and Li et al [31] were similar to ours.…”
Section: Discussionsupporting
confidence: 82%
“…Previous meta-analyses on this topic have yielded conflicting results [28][29][30][31][32]. The results of metaanalyses by Xiang et al [28], Liu et al [30], and Li et al [31] were similar to ours. However, a meta-analysis by Zhang et al [29] reported a significant association between TGF-β1 C-509T variants and decreased HCC susceptibility, and another meta-analysis by Guo et al [32] demonstrated a close association between TGF-β1 C-509T variants and increased HCC susceptibility.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, recent case-control study as well as metaanalysis have shown no association of TGF β1 -509T*C with the risk of hepatocellular carcinoma or overall cancer risk (Liu et al, 2012;Shi et al, 2012). However, some studies have reported that TGF-β1 *29C was protective against breast cancer and suggested that *29C is a protective allele and *29T a risk allele by showing that the individuals with C/C genotype had a significantly lower risk of developing breast cancer compared to those with the T/T or T/C genotype (Ziv et al, 2001;Hishida et al, 2003;Joshi et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Recently, several groups have used meta-analysis to investigate the association between cancer risk and gene Single nucleotide polymorphisms (SNP) involved in TGF-β signaling (Huang et al, 2010;Huang et al, 2011;Liu et al, 2012). As one of the key effectors of TGF-β signaling, TGFBR2 mediates the growth-inhibitory signals from TGF-β through a complex with TGFBR1 (Derynck and Zhang, 2003;Ikushima and Miyazono, 2010).…”
Section: Discussionmentioning
confidence: 99%